Efficient evaluation of Top-k Skyline queries. - Goncalves, Marlene; Vidal, María Esther (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Emerging technologies have made available very large data repositories, which may be unreliable for a given preference criteria. In order to be able to process these repositories, users may need to discard useless information based on some preference conditions. Different preference-based query languages have been defined to support the bases for discriminating poor quality data and to express user”™s preference criteria. In this paper, we consider the preference-based query language, “Top-k Skyline”, which combines the order-based and score-based paradigms. Thus, “Top-k Skyline” is able to identify the top-k objects w.r.t. a score function f among the ordering induced by a multicriteria function m. Several algorithms have been proposed to implement these two paradigms independently; however, the problem of efficiently evaluating “Top-k Skyline” queries remains open. In this work, we propose evaluation strategies for “Top-k Skyline” queries and we report initial experimental results that show the properties of our proposed solutions.